An experimental study on the use of fibrin glue in corneal wound repair in rabbits - Ali Hassan Abdullah, Alashw Al (2009)
To evaluate the clinical outcomes and histopathological changes after using fibrin glue for repairing different types of corneal wound in rabbits. Ten rabbits were involved in this study. They were divided into two groups A and B, with each group consisting of 5 rabbits. Full thickness central corneal wound of 6 mm in length was performed in group A and peripheral wound of 6 mm was made in group B. The wounds then were closed using the fibrin glue. Serial clinical examination was conducted using portable Slit-lamp at day 1, 3, 7, 14 and day 21 post procedure to evaluate wound opposition, corneal clarity and anterior chamber depth. Enucleation was done on day 21 of study. Histopathology evaluation was performed to look for stromal inflammation, vascularization, granuloma formation and microscopic wound gapping. Eighty percent of eyes in group A achieved good wound opposition by first day and 100% by third day post surgery. No wound leak was reported in group B throughout duration of study. Clear cornea with deep anterior chamber obtained in all subjects at the end of study. Histopathology examination revealed stromal vascularization of scanty degree in group B. Majority of subjects had shown mild inflammatory reaction but no granuloma formation or microscopic wound gapping was reported in the two groups of study.